Diversity of Eukaryotic DNA Replication Origins Revealed by Genome-Wide Analysis of Chromatin Structure - Berbenetz, Nicolas M. (Public Library of Science, 2010)
Eukaryotic DNA replication origins differ both in their efficiency and in the characteristic time during S phase when they become active. The biological basis for these differences remains unknown, but they could be a consequence of chromatin structure. The availability of genome-wide maps of nucleosome positions has led to an explosion of information about how nucleosomes are assembled at transcription start sites, but no similar maps exist for DNA replication origins. Here we combine high-resolution genome-wide nucleosome maps with comprehensive annotations of DNA replication origins to identify patterns of nucleosome occupancy at eukaryotic replication origins. On average, replication origins contain a nucleosome depleted region centered next to the ACS element, flanked on both sides by arrays of well-positioned nucleosomes. Our analysis identified DNA sequence properties that correlate with nucleosome occupancy at replication origins genome-wide and that are correlated with the nucleosome-depleted region. Clustering analysis of all annotated replication origins revealed a surprising diversity of nucleosome occupancy patterns. We provide evidence that the origin recognition complex, which binds to the origin, acts as a barrier element to position and phase nucleosomes on both sides of the origin. Finally, analysis of chromatin reconstituted in vitro reveals that origins are inherently nucleosome depleted. Together our data provide a comprehensive, genome-wide view of chromatin structure at replication origins and suggest a model of nucleosome positioning at replication origins in which the underlying sequence occludes nucleosomes to permit binding of the origin recognition complex, which then (likely in concert with nucleosome modifiers and remodelers) positions nucleosomes adjacent to the origin to promote replication origin function.